2013
DOI: 10.1007/s00415-013-7138-1
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of cognitive and psychiatric functions in spinocerebellar ataxia types 1 and 2

Abstract: The role of the cerebellum in cognition, both in healthy subjects and in patients with cerebellar diseases, is debated. Neuropsychological studies in spinocerebellar ataxia type 1 (SCA1) and type 2 (SCA2) demonstrated impairments in executive functions, verbal memory, and visuospatial performances, but prospective evaluations are not available. Our aims were to assess progression of cognitive and psychiatric functions in patients with SCA1 and SCA2 in a longitudinal study. We evaluated at baseline 20 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
61
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 55 publications
9
61
0
Order By: Relevance
“…These abnormalities are similar to the cognitive alterations were found in SCA1 (executive dysfunction) and SCA2 and 3 (executive and visuospatial disabilities) [3,4]. This may reflect the disturbance of the cerebellar-prefrontal connection system [33,34] [39,40].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…These abnormalities are similar to the cognitive alterations were found in SCA1 (executive dysfunction) and SCA2 and 3 (executive and visuospatial disabilities) [3,4]. This may reflect the disturbance of the cerebellar-prefrontal connection system [33,34] [39,40].…”
Section: Discussionsupporting
confidence: 58%
“…The main neurological symptoms are gait and limb ataxia and dysarthria, accompanied by additional neurological signs, which are variable and often overlapping within the subtypes of the group. The characteristic cognitive abnormalities are executive dysfunction and visuospatial disability in the most common SCAs (SCA1, 2 and 3) [3,4]. The genetic diversity of SCAs comprises trinucleotide repeat expansions (SCA1, 2, 3, 6, 7, 8, 12, 17 and dentatorubral-pallidoluysian atrophy), pentanucleotide repeat expansions (SCA10 and 31), hexanucleotide repeat expansions (SCA36) and conventional mutations (SCA5, 11, 13, 14, 15/16, 18, 19/22, 21, 23, 26, 27, 28, 29, 34, 35, 38 and 40), whereas the responsible gene has not yet been identified in some forms of SCAs (SCA4, 20, 25, 30, 32 and 37) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous resting state functional MRI studies also observed the associations between the lingual gyrus and psychiatric symptoms such as depression, loneliness, and anxiety (Lan et al., 2015; Liu et al., 2015, 2017). Although psychiatric symptoms were not reported in the five included studies, they are common in SCA2 patients (Alves‐Cruzeiro, Mendonca, Pereira, Almeida, & Nobrega, 2016; Fancellu et al., 2013; Schmitz‐Hübsch et al., 2011). Therefore, the lingual gyrus may also play a role in emotional processing.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive deficits in moderate stage of the disease are broad and concern several domains, including executive function, fluid intelligence, verbal memory, visuo‐spatial abilities 62, 64, 65, 66, 67…”
Section: Cognitionmentioning
confidence: 99%
“…On the other hand, infantile forms that are characterized by larger expansions have marked cognitive impairment. Lack of association between motor dysfunction and cognitive impairment has been reported 43, 67, 69…”
Section: Cognitionmentioning
confidence: 99%